INDIGENOUS LANGUAGE AND MORAL : CULTURAL AND EDUCATIONAL IMPLICATIONS OF TWO TIMELESS VIETNAMESE COLONIAL TEXTBOOKS - Bui, Thai (My University, 2022)
Indigenous Language and Moral are two series of textbooks implemented in Franco-Vietnamese elementary schools during the early twentieth century, when the territory of today’s Vietnam was in part a French colony and in part French protectorates. The historical, cultural, and educational conditions in which the books were created have long become obscure, yet the books themselves have not. Instead, they have left the classroom walls to enter the twenty-first century publishing industry as children’s literature, despite their textbook format. This study examines the publisher’s reasons for their repeated republications during the 2000s and 2010s and systematically categories their moral topics in an attempt to understand their educational and cultural relevance in modern Vietnamese society. Findings suggest that the books’ moral themes are in fact more compatible with the values upheld by the modern society than with the modern education program offered by the national curriculum. Although this thesis might be the first English-language study that took interest in the phenomenon of these books’ seemingly timeless survival, it is my hope that it will not be the last, but rather an inspiration for further, more comprehensive research into said phenomenon.
Keywords: children’s books, children’s literature, colonial education, colonial legacy, Indigenous Language Textbook, Moral Textbook, moral content, moral education, moral values, post-colonial, textbook analysis, Tran Trong Kim, Vietnam